MANAJEMEN PEMERINTAH KOTA PEKANBARU DALAM PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KOTA PEKANBARU 2015 - Egi Syahyudi; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Micro, Small and Medium Enterprises (UMKM) have a strategic role in addressing unemployment and poverty. However, if the management is not done professionally, then the established cooperative or business entity will not progress and develop. Pekanbaru as the capital of the Riau province became the center of the Riau province, is expected to be a common example for the empowerment of UMKM in Kabupaten / Kota Riau province. There are 4 different efforts of the Cooperative Office and UMKM of Pekanbaru City in the empowerment of SMEs that consist of legality, market strengthening, access to capital, and assistance. The results of the research are seen from the Government Planning in the Empowerment of Small and Medium-Sized Micro-enterprises (UMKM) in Pekanbaru City, the government has set up a five-year strategic plan (Renstra) with goals and objectives that are considered to be the right target in empowering UMKM.Keywords: Government Management, Empowerment of UMKM